THE ESSENCE AND SIGNIFICANCE OF THE CONCEPT OF ENSURING FREEDOM OF CONSCIENCE OF CITIZENS AND STATE POLICY IN THE RELIGIOUS SPHERE IN THE REPUBLIC OF UZBEKISTAN - Turdieva Dilafruz Makhmudjanovna (Sciental Journals Publishing, 2025)
This article analyzes the "Concept of Ensuring Freedom of Conscience of Citizens and State Policy in the Religious Sphere in the Republic of Uzbekistan," approved by Law No. ORQ-1037 of the Republic of Uzbekistan dated February 25, 2025. It examines the concept's goals, objectives, principles, and priority areas, as well as the fundamental notions defined within it (freedom of conscience, secularism, secular state). The article also discusses the mechanisms for implementing the concept and the expected outcomes and evaluates its significance in the reforms of Uzbekistan's religious and educational sphere.
Keywords: Freedom of conscience, state policy in the religious sphere, secularism, secular state, interfaith harmony, religious tolerance, countering religious radicalization.